2019
DOI: 10.1002/bip.23266
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of polypeptoid chain configurations

Abstract: Like polypeptides, peptoids, or N‐substituted glycine oligomers, have intrinsic conformational preferences due to their amide backbones and close spacing of side chain substituents. However, the conformations that peptoids adopt are distinct from polypeptides due to several structural differences: the peptoid backbone is composed of tertiary amide bonds that have trans and cis conformers similar in energy, they lack a backbone hydrogen bond donor, and have an N‐substituent. To better understand how these diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 39 publications
(52 reference statements)
5
65
1
Order By: Relevance
“…Initial coordinates for MD simulations were generated with all backbones in the cis -amide conformation as suggested in recent studies (18, 21). The backbone Φ and Ψ angles of the Cα alternated between Z Rc (∼90, ∼150) and Z Sc (∼−90, ∼−150) (22). Peptoid chains were arranged in blocks of 12 stacked parallel in the a dimension, with these blocks arranged ether parallel or antiparallel to one another in the c dimension to form a periodic monolayer configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Initial coordinates for MD simulations were generated with all backbones in the cis -amide conformation as suggested in recent studies (18, 21). The backbone Φ and Ψ angles of the Cα alternated between Z Rc (∼90, ∼150) and Z Sc (∼−90, ∼−150) (22). Peptoid chains were arranged in blocks of 12 stacked parallel in the a dimension, with these blocks arranged ether parallel or antiparallel to one another in the c dimension to form a periodic monolayer configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the spread in dihedral angles was very narrow for both of these residues, and they populate the known energy minima of the Ac‐Sar‐Sar‐N(Me) 2 Ramachandran plot . Specifically, residue 2 and residue 3 occupy the Z Rt and Z Sc conformations, respectively …”
Section: Resultsmentioning
confidence: 93%
“…A recent analysis of torsion angles reported in high‐resolution peptoid structures revealed that the majority of the recorded ϕ and ψ dihedral angles are clustered in confined spaces of the Ramachandran plot that are mirror images of one another (ϕ ≈ 70°, ψ ≈ 180°, and ϕ ≈ –70°, ψ ≈ 180°), independently from the cis or trans amide bonds geometry of the oligomeric species (Figure A). Interestingly, similar values for ϕ and ψ torsion angles have also been found in polyproline type I (PPI, ϕ ≈ –75°, ψ ≈ 160°) and type II (PPII, ϕ ≈ –75°, ψ ≈ 145°) helices (both showing amide bonds with p S planar chirality).…”
Section: Synthesis and Structural Properties Of Cyclic Peptoidsmentioning
confidence: 94%